Some Factors Affecting Undergraduate Academic Achievement - Hunter, R. C. A. (1965)
A related series of studies, most of which have been published previously, is described. These studies form a coherent whole and demonstrate the development of a theme, namely, the identification of factors in the student and the medical school which, in their interaction, influenced undergraduate academic performance at one medical school. In the population concerned no reliable positive or negative correlation could be demonstrated between cognitive ability and academic performance, when the former was measured by the Wechsler Adult Intelligence Scale and the Medical College Admission Test, and the latter by the current assessment methods of the medical school. Other factors, including socioeconomic and individual personality variables, are at present under investigation as to their effect on academic achievement. It is emphasized that the results of these studies cannot be regarded as valid for all medical schools, but the methods employed can be generalized.